PARADIGMA KEKERASAN AGAMA - Akhyar Akhyar (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2009)
The doctrine as contained in the Qur'an ond Sunnah is a doctrine that is a universal and has been covering every aspect of human life. universality of the quran and sunnah are meaningful efect without being limited by space and time. therefore obedience to god and the belief that god has revealed i will be a universal will to to men. this attitude does trend to the doctinaire attitude that is based on a strong desire to maintain and uphold the teachings of religion which is free of interpretations that can mislead people. but this tendency can sometmes lead to the universal doctrine that particular yhus making loss of identity because religion can ot follow the process of change adaptation and acculturation